Eribulin in Male Patients With Breast Cancer: The First Report of Clinical Outcomes. (14th October 2016) - Giotta, Francesco; Acito, Luigi; Candeloro, Giampiero; Del Medico, Pietro; Gadaleta‐Caldarola, Gennaro; Giordano, Guido; Gueli, Rossana; Lugini, Antonio; Magri, Valentina; Mandarà, Marta; Masci, Giovanna; Pisconti, Salvatore; et al.
Abstract : Background: Evidence on the management and treatment of male breast cancer is scant. We report the analysis of a multicenter Italian series of patients with male breast cancer treated with eribulin. To our knowledge, this is the first report on the use or eribulin in this setting. Patients and Methods: Patients were retrospectively identified in 19 reference centers. All patients received eribulin treatment, according to the standard practice of each center. Data on the identified patients were collected using a standardized form and were then centrally reviewed by two experienced oncologists. Results: A total of 23 patients (median age, 64 years; range, 42–80) were considered. The median age at the time of diagnosis of breast cancer was 57 years (range, 42–74). HER2 status was negative in 14 patients (61%), and 2 patients (9%) had triple‐negative disease. The most common metastatic sites were the lung ( n = 14; 61%) and bone ( n = 13; 56%). Eribulin was administered for a median of 6 cycles (range, 3–15). All patients reported at least stable disease; two complete responses (9%) were documented. Eribulin was well‐tolerated, with only four patients (17%) reporting grade 3 adverse events and two (9%) with treatment interruptions because of toxicity. Eight subjects (35%) did not report any adverse event during treatment. For patients with a reported fatal event, the median overall survival from the diagnosis of metastatic disease was 65 months (range, 22–228). Conclusion: Although hampered by all the limitations of any retrospective case series, the results of the present study suggest, for the first time, the use of eribulin as therapy for male breast cancer. Implications for Practice: Evidence on the management and treatment of male breast cancer is eagerly awaited. Although hampered by all the limitations of any retrospective case series, the results of the present study suggest, for the first time, the use of eribulin as therapy for male breast cancer. Abstract : Analysis of a multicenter Italian series of patients with male breast cancer treated with eribulin is reported. Patients were retrospectively identified from 19 reference centers. Eribulin was well‐tolerated, with few adverse events. The results of the present study suggest the use of eribulin as therapy for male breast cancer.